ChemInform Abstract: Aryl Amination Using Ligand‐Free Ni(II) Salts and Photoredox Catalysis. Issue 50 (November 2016) - Corcoran, Emily B.; Pirnot, Michael T.; Lin, Shishi; Dreher, Spencer D.; DiRocco, Daniel A.; Davies, Ian W.; Buchwald, Stephen L.; MacMillan, David W. C.
Abstract: A light‐mediated aryl amination is developed using a combination a NiBr2 (dme) or NiCl2 (dme) and iridium complex IRCP as catalytic system.